Electroplating : basic principles, processes and practice. - Kanani, Nasser, ....- (Oxford : Elsevier, 2004)
"Electroplating: Basic Principles, Processes and Practice" offers an understanding of the theoretical background to electroplating, which is essential if the practical results are to be as required. This book is different in that it explains how the electrodeposition processes work, covering such topics as the elctrodeposition of composites, multilayers, whisker formation and giant magnetoresistive effects. The section on R&D approaches will be especially useful for organisations in the field. This is the first English language version of a well-known German language book from a prestigious author of international repute. "Electroplating" is an invaluable resource for manufacturers of coatings, electrochemists, metal finishers and their customers and academics in surface engineering. It offers an understanding of the theoretical background to electroplating. It explains how the electrodeposition processes work.
Keywords: Metalen; Oppervlaktebehandeling